Pengembangan Media Pembelajaran KIS_U (Akidah Seru) Berbasis iSpring Suite pada Kelas X di MAN 9 Jombang - Mu’tabaroh, Robiatul; Rohmah, Hidayatur (YASIN, 2025)
Learning of Akidah Akhlak in schools is still dominated by lecture methods and conventional media such as textbooks and student worksheets (Lembar Kerja Siswa, LKS), resulting in low student engagement and interest. This study aims to develop an Android-based learning medium called KIS_U (Akidah Seru) using the iSpring Suite application to create more engaging and interactive learning. The method applied was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, involving 30 Grade X students of MAN 9 Jombang selected through purposive sampling. Data were collected through interviews, observations, and validation by media and content experts. Validation results indicated feasibility ratings of 91% from media experts and 95–98% from content experts, both categorized as “highly valid.” KIS_U was found effective in increasing student engagement and aiding material comprehension. The study concludes that KIS_U is suitable for use as an innovative alternative in Akidah Akhlak learning. The implication is that integrating interactive technology into religious education has the potential to enhance learning quality while encouraging students to learn more actively and enjoyably.